A Bacterium Isolated From Soil in a Karst Rocky Desertification Region Has Efficient Phosphate-Solubilizing and Plant Growth-Promoting Ability - Xie, Jinge; Yan, Zongqiang; Wang, Guifen; Xue, Wenzhi; Li, Cong; Chen, Xiwen; Chen, Defu (Frontiers in Microbiology, 2021)
The phosphorus in the soil available to plant can easily be combined with calcium ion, whose content is high in karst rocky desertification (KRD) regions, thereby resulting in a low utilization efficiency of phosphorus. Application of phosphate-solubilizing bacteria (PSB) from the KRD region would facilitate enhanced phosphate availability in the soil. In the present study, the strains belonging to Acinetobacter, Paraburkholderia, and Pseudomonas with efficient phosphate-solubilizing ability were isolated from fruit tree rhizosphere soils in KRD regions. Particularly, Acinetobacter sp. Ac-14 had sustained and stable phosphate-solubilizing ability (439–448 mg/L, 48–120 h). Calcium carbonate decreased the phosphate-solubilizing ability in liquid medium; however, it did not affect the solubilization index in agar-solidified medium. When cocultivation with Arabidopsis thaliana seedling, Ac-14 increased the number of lateral roots, fresh weight, and chlorophyll content of the seedlings. Metabolomics analysis revealed that Ac-14 could produce 23 types of organic acids, majorly including gluconic acid and D-(-)-quinic acid. Expression of Ac-14 glucose dehydrogenase gene (gcd) conferred Pseudomonas sp. Ps-12 with sustained and stable phosphate-solubilizing ability, suggesting that the production of gluconic acid is an important mechanism that confers phosphate solubilization in bacteria. Moreover, Ac-14 could also produce indole acetic acid and ammonia. Collectively, the isolated Ac-14 from KRD regions possess efficient phosphate-solubilizing ability and plant growth-promoting effect which could be exploited for enhancing phosphorus availability KRD regions. This study is significance for the improvement of soil fertility and agricultural sustainable development in phosphorus-deficient KRD regions.